2004
DOI: 10.1097/00129492-200403000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Intralabyrinthine Schwannomas: Diagnosis, Management, and a New Classification System

Abstract: Intralabyrinthine schwannomas are uncommon tumors that mimic the clinical features of many other neurotologic conditions. A high index of suspicion and precise imaging are often required to detect these tumors. Surgical treatment is indicated for specific indications and will be needed in the minority of patients with this disorder. The classification system that we propose is helpful in both the diagnosis and the management of these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
173
2
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(190 citation statements)
references
References 31 publications
3
173
2
12
Order By: Relevance
“…Hence, detection of growth is helpful in triaging patients to treatment. In the series published by Kennedy et al, 23 only 3 (15%) of the 20 cases that had MR follow-up (FU) showed increase in size. These 3 lesions had an IAC component at presentation and, therefore, did not match the above-described stringent criteria of ILS.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, detection of growth is helpful in triaging patients to treatment. In the series published by Kennedy et al, 23 only 3 (15%) of the 20 cases that had MR follow-up (FU) showed increase in size. These 3 lesions had an IAC component at presentation and, therefore, did not match the above-described stringent criteria of ILS.…”
mentioning
confidence: 99%
“…A limited number of reports, mainly case reports and small series of less than 10 subjects, described the imaging findings of ILSs. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] One larger series of 28 cases published by Kennedy et al 23 focused on management and classification of these lesions. However, only 15 cases of this series met the above-described stringent criteria of ILS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In subacute and chronic labyrinthitis, calcification or fibrosis often replaces the labyrinth fluid, but the edges of the lesion are not well defined [9] . Serial MRI detects any growth of the neoplasm (even if rare) and represents the key step in the management of schwannoma according to Kennedy et al [1]. In our case, serial MRI revealed no significant growth over 3 years of follow-up.…”
Section: Discussionmentioning
confidence: 48%
“…Schwannoma is the most common benign neoplasm affecting the internal auditory canal (IAC) and pontocerebellar angle, and it accounts for up 6% of all intracranial tumors [1,2] . Intralabyrinthine schwannoma (ILS) is a subtype of schwannoma that originates from the perineural Schwann cells of the vestibulocochlear nerve proximal to the membranous labyrinth (cochlea and vestibule), without any outer extension [3] .…”
Section: Introductionmentioning
confidence: 99%